Method of the shortcut estimation of rails reliability by the fatigue strength criterion - Sosnovskii, L.A.; Makhutov, N.A.; Matviatsov, V.I.; Kebikov, A.A. (Проблемы прочности, 2009)
The diagram of damage of structural steels under bending and contact loading has been constructed. The criterion of the critical state of steels is proposed, which corresponds to the formation of incipient surface cracks in the rolling friction zone. The methods of shortcut estimation of the damaged state of railway rails, which provide prediction of their reliability and life under service conditions, are proposed. A set of experimental studies is made with objectives to justify the proposed diagram, criterion and methods. Описана процедура построения диаграммы повреждаемости конструкционных сталей при нагружении изгибной и контактной нагрузками. Предложены критерий критического состояния для сталей, который соответствует условию формирования поверхностных трещин в зоне трения качения, и методы ускоренной оценки поврежденного состояния железнодорожных рельсов, позволяющие прогнозировать их надежность и долговечность при эксплуатационном нагружении. Выполнена серия экспериментов, что дает возможность обосновать предложенные диаграмму, критерий и методы.